Effects of Radiation on Materials: 19th International Symposium 2000
DOI: 10.1520/stp12407s
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step Recovery Process of Irradiation Hardening in 1%Ni Doped 9%Cr-2%W Martensitic Steel

Abstract: The effect of nickel addition on irradiation-induced hardening has been investigated for reduced-activation martensitic steel (RAMS). Specimens were irradiated in the JMTR at 80°C and 220°C up to 0.15 dpa. There was no significant difference in the tensile properties between the steels with and without Ni addition after the irradiation at 220°C, while in the case of the irradiation below 170°C, the Ni-added RAMS showed a more than four times larger irradiation hardening than the steel without Ni addition. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…However, post-irradiation annealing recovery behavior of irradiation hardening investigated in the previous work suggested that irradiation induced ''nickel-related phase'' would be produced and be stable only at relatively low temperature less than about 543 K. 10) Further investigation is needed for the invisible factor.…”
Section: Relation Between Microstructural Evolution Andmentioning
confidence: 93%
See 1 more Smart Citation
“…However, post-irradiation annealing recovery behavior of irradiation hardening investigated in the previous work suggested that irradiation induced ''nickel-related phase'' would be produced and be stable only at relatively low temperature less than about 543 K. 10) Further investigation is needed for the invisible factor.…”
Section: Relation Between Microstructural Evolution Andmentioning
confidence: 93%
“…Furthermore, we pointed out that the irradiation hardening of RAF steel with a nickel addition was much larger than that of RAF steel without nickel addition when the irradiation temperature was relatively low. 9,10) Thus, effects of nickel in itself on the microstructure evolution and the mechanical properties in RAFSs after irradiation should be evaluate for understanding helium effects on embrittlement when the NIT method are applied. In the present study, therefore, we investigated the effect of a nickel addition on the microstructure evolution and the mechanical properties in RAF steel irradiated in the ATR-A1 with low level of helium generation.…”
Section: Introductionmentioning
confidence: 99%
“…7. 43) Examinations by TEM revealed that the size and number density of dislocation loops were smaller and higher in the steel added with nickel, indicating that the large irradiation hardening observed in the nickel added steel is due to increase in the number density of dislocation loops. It is expected that ironnickel dumbbell is more stable and enhances to form smaller dislocation loops in a high density, which induce larger hardening.…”
Section: Ni Addition Techniquementioning
confidence: 96%
“…(2) Helium and hydrogen effect Simulation irradiations using B-doping, Ni-doping and 56 Fe-doping have been conducted to investigate He and H effects [11,[14][15][16][17][18][19][20]. In these simulation methods, Ni-doping has some side effects, so that it is difficult to evaluate the helium effect itself [11,16,17].…”
Section: Issues To Be Investigatedmentioning
confidence: 99%
“…In these simulation methods, Ni-doping has some side effects, so that it is difficult to evaluate the helium effect itself [11,16,17]. B-doping results suggest He up to 300 appm does not affect hardening, but it does increase the DBTT.…”
Section: Issues To Be Investigatedmentioning
confidence: 99%